HUBUNGAN ANTARA KONFORMITAS DENGAN PERILAKU KONSUMTIF PADA MAHASISWA DI GENUK INDAH SEMARANG - Fitriyani, Nur; Widodo, Praseetyo Budi; Fauziah, Nailul (Jurnal Psikologi, 2013)
National development in Indonesia brings change habits become increasingly lavish lifestyle that leads to consimptive behavior. Student as teenager was also affected. Consumptive behavior is the behavior of consumer into buying that not based on need but desires of the irrational and excessive. Consumptive behavior is influence by motivation, self esteem, observation, learning process, personality, self concept, lifestyle, culture, sosial class, reference group and family. Student perform a variety of adjustment to gain acceptance of friend boarding as reference group, which encourages student to conformity with the group. Conformity is a behavior adjusment to gain acceptance in group. This study used 130 student boarding at Genuk Indah housing as a research subject. Subjects were taken using proportional random sampling technique. Methods of data collection in this study are using two scales, namely the conformity scale and consumptive behavior scale. The results of regression analysis with simple analytical methods is rxy = 0,333 with p = 0.000 (p <0.05). The direction of the positive relationship between two variables means that the highly the student conformity, the consumptive behavior will be highly. The conformity provide an effective contribution of 10,9% on consumptive behavior